EKSISTENSI HUKUM KEWARISAN ISLAM DALAM PEMBAGIAN WARISAN MASYARAKAT BUGIS BONE (Studi di Kecamatan Tanete Riattang) - Asni Zubair (Al-Mizan (e-Journal), 2022)
The property of the deceased person becomes an inheritance for his heirs. The purpose of this paper is to analyze the implementation of the inheritance distribution of the Bugis Bone community, Tanete Riattang District by looking at the reasons that the community has for distributing inheritance in Tanete Riattang District. This research is a field study with an empirical normative approach. Data were collected through observation and interviews, then analyzed by qualitative description. The results showed that the Bugis Bone community, Tanete Riattang District, used an Islamic inheritance system in the distribution process. In addition, the application of customs in the inheritance of the Bugis Bone community is also carried out, for example, those that do not include heirs. The heirs conduct deliberation and are given the inheritance to be a form of affection.